‘We Only Smile’: A Study of Perceived Discrimination among Asian Female Muslim Tourists - Ulinnuha, Hana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This chapter examines how Asian female Muslim tourists encountered negative and discriminatory experiences when they interacted with the locals during holidays in Europe, particularly The Netherlands. This is especially the case for female Muslims who wear the veil. The negative and discriminatory experiences encountered by these female Muslim tourists include gazes from locals, treated unfairly, negative remarks, and fall under suspicions. However, in hardly any case, these female Muslims "labelled" the event as discrimination and associated it to their identity as a Muslim. These female Muslim tourists employed a variety of coping strategies that comprise direct confrontation, accepting & ignoring discrimination, apologizing, justifying discrimination & thinking positively, modifying behaviour. There is a general attitude among these tourists about negotiating the negatively and discriminatory experiences: that they want to deal with it in a subtle way, such as by smiling.